Metronidazole in prevention and treatment of bacteroides infections after appendicectomy. Issue 6005 (7th February 1976) - Willis, A T; Ferguson, I R; Jones, P H; Phillips, K D; Tearle, P V; Berry, R B; Fiddian, R V; Graham, D F; Harland, D H; Innes, D B; Mee, W M; Rothwell-Jackson, R L; et al.
Abstract : The frequency of non-clostridial anaerobic infection was studied in 95 patients who had undergone acute appendicectomy: 49 received prophylactic metronidazole and 46 received placebo. Anaerobic infection did not develop in any of the metronidazole-treated patients, but infections did develop in nine (19%) of the 46 controls. Metronidazole is conveniently administered by suppository to patients who cannot take oral drugs. Five patients with intra-abdominal infections caused by non-clostridial anaerobes were successfully treated with metronidazole.